2015
DOI: 10.1038/srep08931
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Receptor for Advanced Glycation End Products in Airway Inflammation in CF and CF related Diabetes

Abstract: Cystic Fibrosis (CF) is often accompanied by diabetes leading to worsening lung function, the reason for which is unclear. The receptor for advanced-glycation-end-products (RAGE) regulates immune responses and inflammation and has been linked to diabetes and possibly CF. We performed a pilot study to determine if CF and CF-related diabetes (CFRD) are associated with enhanced RAGE expression. Full length (fl)RAGE, soluble (s)RAGE, endogenous soluble (es)RAGE, S100A12 (enRAGE) and advanced-glycation-end-products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
3
34
1
Order By: Relevance
“…sRAGE acts as a decoy of RAGE signaling, thereby inhibiting the interaction between RAGE and proinflammatory ligands (such as HMGB1 and AGEs), which have been proposed to play critical roles in multiple inflammatory diseases [23,29,30]. Low sRAGE levels have been reported in studies of individuals with inflammatory lung diseases, such as COPD [25,31], asthma [32], and cystic fibrosis [33]. Consistent with these findings, we found that serum levels of sRAGE were decreased in patients with silicosis.…”
Section: Discussionsupporting
confidence: 89%
“…sRAGE acts as a decoy of RAGE signaling, thereby inhibiting the interaction between RAGE and proinflammatory ligands (such as HMGB1 and AGEs), which have been proposed to play critical roles in multiple inflammatory diseases [23,29,30]. Low sRAGE levels have been reported in studies of individuals with inflammatory lung diseases, such as COPD [25,31], asthma [32], and cystic fibrosis [33]. Consistent with these findings, we found that serum levels of sRAGE were decreased in patients with silicosis.…”
Section: Discussionsupporting
confidence: 89%
“…It has been hypothesized that elevated sputum glucose found in CFRD could be a carbon source that would support increased bacterial growth and lead to pulmonary exacerbations. In support of this hypothesis, measured sputum glucose concentrations are very low and often below detection, suggesting glucose is being consumed in the sputum either by infecting microbes or the host inflammatory cells . The glucose concentration in sinus secretions in the context of CFRD has not been described, although similar pathophysiology could be at play.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for blockade of RAGE signal transduction is supported by work in a variety of preclinical disease models such as diabetes and its complications, Alzheimer’s disease 53 54 , cardiovascular disease 42 44 55 56 , immune/inflammatory disorders 57 58 and cancer 59 60 , as examples. RAGE ligands accumulate in these settings and therefore their contribution to the pathogenesis of cellular dysfunction and tissue damage in these diseases may ultimately be mitigated by modulation of RAGE signaling.…”
Section: Discussionmentioning
confidence: 99%